Consulting report - Gloria S.A. - Pajares Correa, Brian; Tami Estrada, Fiorella (Pontificia Universidad Católica del Perú, 2018)
This consulting report was elaborated in order to find a solution for the problem proposes by the metal packaging managers of Gloria S.A. The main problem is the lack of presence of the Gloria´s metal packaging business in other countries of the region. The purpose is to increase the presence of the business through the expansion of Gloria´s metal packaging business to other countries of the region. The objective for this report is to obtain a final recommendation of where to expand Grupo Gloria´s metal packaging business, how to implement it and the key success factors for the project in order to guarantee the success of the project. This report includes the result of an exhaustive analysis of the current situation of the country using the PESTE information and of the metal packaging industry in Mexico, Argentina, Chile, Colombia, and Bolivia. As a result of this analysis Colombia got the highest score with 2.98 points out of 4. Considering the results of the previous evaluation, the best solution is to find more presence in the region by expanding the metal packaging business of Gloria to Colombia. This is because of the attractiveness of its market and the high possibilities of success due to the support of other parties; because Grupo Gloria already has operations in this country; and due to the amounts of investment required that can be aligned to the investment that the company is willing to confront. Moreover, this project presents an implementation plan for the next 17 months that are on hands of the metal packaging team of Peru. This plan considered the next steps that are needed in order to increase the presence of Gloria´s metal packaging business in other countries of the region. The investment of the implementation it’s around 34 million dollars. However, it depends in the further decisions that will be taken.

El siguiente reporte de consultoría fue elaborado para encontrar una solución al problema propuesto por el los gerentes del equipo de empaques de metal de Gloria S.A. El principal problema es la falta de presencia del negocio de empaques de metal de Gloria S.A. en otros países de la región. El final objetivo de este reporte es obtener una recomendación final sobre el mejor entorno en Latinoamérica para la expansión del negocio de empaques de metal de Gloria S.A., como implementar la propuesta y los factores claves de éxito para garantizar el logro del proyecto. Este reporte incluye el resultado de un análisis profundo de la situación actual del país a través de un análisis PESTE y un análisis de la industria de empaques de metal en México, Argentina, Chile, Colombia y Bolivia. Como resultado Colombia obtuvo el mayor puntaje con 2.98 puntos sobre 4. Considerando el resultado anterior, la mejor solución es expandir el negocio de empaques de metal a Colombia, debido a que es el mercado más atractivo, además, Grupo Gloria tiene operaciones en el país desde el 2011 y el monto de inversión del proyecto se puede alinear a los niveles de inversión que la empresa está dispuesta a asumir. Este proyecto presenta un plan de implementación para los próximos 17 meses, que están a cargo del equipo de empaques de metal de Perú principalmente. Este plan considera los siguientes pasos a solucionar para poder lograr mayor presencia del negocio de empaques de metal de la empresa Gloria S.A. en la región de Latinoamérica. La inversión para este proyecto es de 34 millones de dólares. Sin embargo, este monto dependerá de las decisiones que se tomen más adelante.
Keywords: Empresas -- Organización; Administración de empresas; Empresas internacionales -- América Latina.; https://purl.org/pe-repo/ocde/ford#5.02.04